2015
DOI: 10.4081/ejh.2015.2455
|View full text |Cite
|
Sign up to set email alerts
|

RANK/RANKL/OPG signaling pathways in necrotic jaw bone from bisphosphonate-treated subjects

Abstract: Osteonecrosis of the jaw (ONJ) is a chronic complication affecting long-term bisphosphonate-treated subjects, recognized by non-healing exposed bone in the maxillofacial region. The pathophysiological mechanism underlying ONJ has not been fully elucidated. The aim of the present study was to investigate the role of RANK/RANKL/OPG signaling pathway and, in parallel, to evaluate angiogenic and matrix mineralization processes in jaw bone necrotic samples obtained from bisphosphonate-treated subjects with establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 45 publications
2
14
0
Order By: Relevance
“…The micro-CT analysis showed that the OVX-veh group had greater bone loss, and this loss was diminished with ZOL treatment at both time points according to previous studies (11). In the sagittal section, the SHAM-ZOL 30 d group had less bone loss in comparison with all of the other groups, most likely as a result of the beneficial effect of estrogen and ZOL in decreasing bone resorption (17).…”
Section: Discussionsupporting
confidence: 60%
“…The micro-CT analysis showed that the OVX-veh group had greater bone loss, and this loss was diminished with ZOL treatment at both time points according to previous studies (11). In the sagittal section, the SHAM-ZOL 30 d group had less bone loss in comparison with all of the other groups, most likely as a result of the beneficial effect of estrogen and ZOL in decreasing bone resorption (17).…”
Section: Discussionsupporting
confidence: 60%
“…Histopathologic Analysis of bone tissue from patients who developed ONJ on DMab for bone metastases revealed a decrease number of osteoclasts with few nuclei. This morpohology is strikingly different from ONJ linked to bisphosphonates where osteoclast numbers are increased with giant, hypernucleated and detached and undergoing apoptosis (16, 45-47). Thus, a careful screening of RA patients for hypocalcemia and ONJ is recommended before DMab administration.…”
Section: Denosumab - Current Indicationsmentioning
confidence: 75%
“…Di Nisio et al ( 34 ) proposed that bacteria in the necrotic area could trigger the RANK/RANKL/OPG signaling pathway. We explored whether serum levels of RANKL and OPG, or the RANKL/OPG ratio had any relationship with the different stages of MRONJ.…”
Section: Discussionmentioning
confidence: 99%